A filosofia como forma de vida: a práxis e a mística em Simone Weil - Dias, Ana Lúcia Guterres (Universidade do Vale do Rio dos Sinos, 2022)
The theme of philosophy as a way of life finds in Simone Weil a philosopher that lived this theme as experience beyond the theoretical speculation.This dissertation has as a goal to research how, in Simone Weil, the philosophy became a way of life. In order to chase this goal we seek to relate the philosophy, the praxis, and the mystique in her philosophical thought and her way of living and of being. We will analyze aspects of her life and philosophical thought as the praxis and the mystique, investigating as they connect to each other establishing the nexus that constitutes her philosophy and life as unique experience and inseparable. Firstly some of the philosopher anthropological assumptions are analyzed, including biographical aspects and foundational concepts in her thought that makes possible a better view from her understanding of the human being. In a second moment we approach the political philosophy as praxis in Simone Weil, analyzing political concepts developed and lived by her. Finally, we examine the philosophy and the mystique in Simone Weil from the connections between both of them and from the study of some mystique concepts thought and experienced by the philosopher, considering that in Simone Weil her philosophycal thought and mystique did not stay restricted to the theoretical area, but both of them came true in the form of concrete experience starting from the problems of the world. We conclude, from the study carried out, that in Simone Weil the philosophy has become a way of living, and at the same time, her way of living has become her philosophy.
Keywords: Simone Weil; Filosofia como forma de vida; Práxis; Mística; Philosophy as a way of life; Praxis; Mystique; ACCNPQ::Ciências Humanas::Filosofia